2019
DOI: 10.13057/biodiv/d200914
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial isolates from bryozoan Pleurocodonellina sp.: Diversity and antimicrobial potential against pathogenic bacteria

Abstract: Abstract. Asagabaldan MA, Bedoux G, Bourgougnon N, Kristiana R, Ayuningrum D, Sabdono A, Trianto A, Radjasa OK. 2019. Bacterial isolates from bryozoan Pleurocodonellina sp.: Diversity and antimicrobial potential against pathogenic bacteria. Biodiversitas 20: 2528-2535.  There is an urgent need to discover new compounds with antibacterial activity, which can be developed into lead structures for the treatment of human disease caused by multidrug-resistant (MDR) bacteria. In this study, we focussed on bryozoan-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Antibacterial activity of the isolates were determined by measuring the diameter of the inhibition zone in mm around the bacterial isolates. The levels of antibacterial activity were categorized as follows: no antibacterial activity (-), 0-1 mm (+), 1-3 mm (++), 3-7 mm (+++) and 7-15 mm (++++) (Asagabaldan et al 2019). The inhibition area was measured to confirm the antibacterial activity (Apsari et al 2019).…”
Section: Screening For Antibacterial Activities Against Mdr Bacteriamentioning
confidence: 99%
“…Antibacterial activity of the isolates were determined by measuring the diameter of the inhibition zone in mm around the bacterial isolates. The levels of antibacterial activity were categorized as follows: no antibacterial activity (-), 0-1 mm (+), 1-3 mm (++), 3-7 mm (+++) and 7-15 mm (++++) (Asagabaldan et al 2019). The inhibition area was measured to confirm the antibacterial activity (Apsari et al 2019).…”
Section: Screening For Antibacterial Activities Against Mdr Bacteriamentioning
confidence: 99%
“…Thus, new antibacterial agents from natural biological sources are required. Biological antibacterial agents can be obtained from honey (Panjaitan et al 2018), mushrooms (Prastiyanto et al 2020b;, isolate bacteria from marine organisms (Asagabaldan et al 2019), bacteriocins (Lestari et al 2019), fruits (Prastiyanto et al 2020d;Wahyuni et al 2019), latex (Prastiyanto et al 2020c) and seeds (Ilvani et al 2019;Prastiyanto et al 2020a). Many studies in the medical field reported the importance of traditional medicinal plants as alternatives of antimicrobial agents (Akhtar and Mirza 2015;Aumeeruddy-elalfi et al 2015;Prastiyanto et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Infections caused by MRSA bacteria consume more health care resources than are consumed by patients infected with non-resistant strains of the same bacteria (Word Health Organization 2018). In consequence, novel antibacterial agents are needed from natural biological sources (Asagabaldan et al 2019;Lestari et al 2019;Prastiyanto et al 2020b;2020a, 2020c. Neutral proteoglycans derived from the P. ostreatus mycelia have been reported that could be used as immunomodulators and anticancer agents (Sarangi et al 2006).…”
Section: Introductionmentioning
confidence: 99%